Influence of Workpiece Tilting Angle on Joint Properties in Tailor Friction Stir Welded Blanks of Aluminium Alloy 5052-H32 - Ro, Chan-Seung; Bang, Hee-Seon; Bang, Han-Sur; Yoo, Seung-Ji; Kim, Jong-Hee; Choi, Eun-Gyeol (Journal of Welding and Joining, 2018)
The application of aluminium tailor-welded blanks (TWB) is progressively increasing in automotive industries due to its high strength to weight ratio, superior corrosion resistance and crashworthiness. The weldments produced by Friction stir welding (FSW) retains high strength and formability as the process yields the sound joints at relatively lower temperatures in comparison to that of the conventional fusion welding processes. However, the FSW of aluminium alloy of different thicknesses in butt configuration is rarely studied. The primary objective of the present work is to investigate the feasibility of FSW process in joining of 1.5 to 2.5 mm thick AA5052 alloy tailored blank by tilting the workpiece with respect to machine bed. The effects of workpiece tilting angle with welding and rotational speeds on mechanical and metallurgical properties of the joints are studied. Minimum effective sheet thickness is found to be around 1.34 mm for tool rotational speed of 400 rpm and tilting angle of 0°. The highest joint strength around 212.6 MPa (95% of base metal strength) is achieved at a workpiece tilt angle of 1° for rotational and travel speed of 400 rpm and 1 mm/s, respectively. The maximum measured hardness is 60 Hv at tool roational speed of 400 rpm with tilting angle of 1°. KCI Citation Count: 0